Length of Time to Get a Job Back During the Covid-19 Pandemic in Badung District - A A I N Marhaeni; Ni Nyoman Yuliarmi; Haris Sanjaya; Ni Made Itarini (International Journal of Social Science and Business, 2023)
The COVID-19 pandemic has impacted the economy, especially the tourism industry, so many employees who have been laid off are now trying to get work opportunities again. This study aims to analyze the simultaneously and partially the effect of gender, age, education, and socioeconomic status of parents on the length of time to get a job again. This research is quantitative research conducted in Badung Regency with a sample of 100 people. The sampling technique is accidental sampling with snowball sampling. The data were collected by using the observation method, especially related to the secondary data needed. There are 2 data analysis techniques used, namely descriptive statistics and inferential statistics. Descriptive statistics are used to describe the variables that have been collected, while the inferential statistics used are moderation regression. The results showed that gender, age, education, and socioeconomic status of parents had a positive effect on the length of time to get a job again. The socioeconomic status of the parents significantly moderated the effect of education on the length of time it took to get a job again. This research is expected to be a strategy to get a job faster after the pandemic.